A Middle Aged Male with Granulomatous Orchitis: Primary Di use Large B-Cell Lymphoma of Testis Mimicking Tubercular Orchitis (The Journal of Ad-din Women's Medical College, 2026)
Primary testicular lymphoma is a rarely seen testicular tumor accounting for 19% of all testicular tumors. It is a rare form of extra nodal non-Hodgkin’s lymphoma representing 1% 2% of non-Hodgkin’s lymphoma. The dominant histological subtype is diffuse large B-cell lymphoma (DLBCL). It is the most common testicular malignancy in men aged over 60 years. Patients with primary testicular DLBCL show a continuously high risk of recurrence with no plateau in the survival curves and a tendency to involve other extra-nodal sites, especially the central nervous system and the contralateral testis. Here we present a 60-year-old gentleman from Bangladesh presenting with fever and unilateral testicular mass for 3 months. Fine needle aspiration cytology (FNAC) from testicular mass revealed granulomatous orchitis and he was started anti tubercular medication without improvement. Later orchiectomy was done and Immunohistochemistry showed diffuse large B-cell lymphoma. He was referred to oncology for further management.The Journal of Ad-din Women's Medical College; Vol. 13 (2), July 2025; p 41-46